The role of mobile technologies in the teaching/learning process improvement in Portugal - Ferreira, Maria João (2015)
Over the past few years, there has been a large investment in information and communication technology in the teaching/learning process. In this context, mobile technologies, including smartphones and tablets emerge as an innovative tool associated with different methods and strategies. Mobile technologies are technological products and, nowadays, a very representative number of so-called "digital generation" own and use them in our day-to-day, in recreational and educational activities. In this way, the mobile technologies contribute to a teaching/learning process more motivating and personalized. The students' motivation increases when this technology is used, leading to greater participation, and, consequently, better and faster acquisition of concepts/skills. Collaborative actions and cooperation between student/student, student/teacher and student/class are increased when mobile devices are used in the classroom context. The use of mobile technologies and their implications for the teaching/learning process are some of the challenges that teachers face today as promoters and "drivers" in this process. To use the tools effectively an understanding is essential and therefore there are implications in teacher training not only for the use and application of technology, but for the underlying concepts and support. This paper examined the evolution of mobile technologies in Higher Education Institutions in Portugal between 2009/2010 and 2014/2015.